The post hatching development of the female genital system in Indigenous Mallard Duck (Anas platyrhynchos): Dhyaa, Ab. Abood and F. J. Al-Saffar - Al-Saffar, F. J. (The Iraqi Journal of Veterinary Medicine, 2015)
The current research aimed at obtaining principal data on the morphological developmental changes that could occur during the post hatching periods in the female genital system of the Indigenous Mallard ducks and to conduct that twenty (immature and mature) ducks were used. Gross findings have revealed that the left ovary in 4 weeks sold ducklings appeared small triangular in shape, located at the dorsal part of coelom in contact caudally with the cranial division of the left kidney and cranially with left lung. In 8 and 12 weeks the left ovary has enlarged showed prominent granular surface. The left oviduct appeared as thin, translucent straighten tube with unapparent regions fixed by a thin doubled folds of oviductal ligament and ureter. In mature and laying ducks, the left ovary was large and irregular in shape, and showed numerous follicles of different developmental stages. The mature and laying left oviduct was fully developed into six well distinguished regions (infundibulum, magnum, isthmus, uterus, junction region and vagina). The present study has concluded that the first twelve weeks of post hatching periods had similar morphological features and showed inert genital organs which were not completely differentiated, while the age of twenty four weeks revealed completely differentiated female genital organs with sexual activity.